An inverse nodal problem for differential pencils with complex spectral parameter dependent boundary conditions - Gulsen, Tuba; Yilmaz, Emrah; Koyunbakan, Hikmet (Mustafa BAYRAM, 2017)
In this study, we are concerned with an inverse nodal problem for second order differential pencil on a finite interval with complex spectral parameter dependent boundary conditions by using nodal points. We give some reconstruction formulas for potential functions  and  as a limit.